Trustworthy Machine Information Behaviour and Open Research Repositories - Simango, Samuel (My University, 2023)
The perception regarding the nature of repository users is changing as a result technological advancements. This is reflected in arguments contending that machines should be recognised as users of library services. Such arguments are based on the view that library collections such as open repositories should be considered as data that can be used by artificially intelligent machine users. These arguments raise questions regarding the concept of trust as they do not actually address attributes that machines users must possess in order for them to be considered trustworthy. This research develops a conceptual framework for understanding the parameters within which trustworthy machine information behavior can emerge. This outcome is achieved by applying machine ethics to a modified version of Wilson's general theory of information behavior that incorporates elements of machine learning. The results indicate that the level of trust placed in machines users is dependent on the algorithms and software used for programming such AI systems as well as the actions of humans who make use of such machine users. In order for any semblance of trust in machine users of open repositories to exist, the machine information behavior employed by the machine users should adhere to certain ethical principles.
Keywords: Machine Information Behaviour; pen Research Repositories; Machine Ethics